FORMULASI DAN EVALUASI SEDIAAN BALSAM AROMATERAPI KOMBINASI MINYAK ATSIRI RIMPANG DLINGO (Acorus calamus) DAN RIMPANG BANGLE (Zingiber purpureum) - Damayanti, Prashinta Nita; Luhurningtyas, Fania Putri; Pujiastuti, Anasthasia; Izzah, Arizul Nurma; Salsabila, Elysa (Jurnal Farmasi Kryonaut, 2026)
Stress and anxiety are mental disorders that can reduce quality of life. Aromatherapy using essential oils is an alternative non-pharmacological therapy to help reduce stress and anxiety. Essential oils from dlingo rhizome (Acorus calamus L.) and bangle rhizome (Zingiber purpureum Roxb.) are known to have relaxing activity, so they have the potential to be developed into aromatherapy balm preparations. This study aims to formulate and evaluate the physical characteristics of aromatherapy balm combined with dlingo rhizome and bangle rhizome essential oils. The preparation was made in five formulas with varying total concentrations of essential oil combinations of 0%, 5%, 10%, 15%, and 20%. Physical evaluation included organoleptic tests, pH, homogeneity, spreadability, and adhesiveness. The results showed that all formulas produced semi-solid, homogeneous preparations, with a white to yellowish color and a distinctive aroma of essential oils that became stronger with increasing concentration. The pH value of all formulas was in the range of 6.13-6.45. The adhesive strength values ​​of Formulas A, B, C, D, and E were 5.00; 2.00; 1.74; 1.37; and 0.66 seconds, while the spreadability values ​​were 2.82; 2.83; 2.94; 2.59; and 2.64 cm. Based on the results of the physical evaluation, all formulas met the organoleptic, homogeneity, and pH requirements. Based on the results of the adhesion test, only Formula A met the adhesive strength requirements for topical preparations (>4 seconds). Based on the results of the spreadability test, all formulas did not meet the reference spreadability for topical preparations used in the study.